Catalytic activity of CuFe2O4 spinel oxide for liquid-phase oxidation of cinnamyl alcohol - Dange, Rutvija M.; Niphadkar, Prashant S.; Bokade, Vijay V.; Nandanwar, Sachin U. (ChemistrySelect, 2022)
CuFe2O4 spinel oxide catalyst was synthesized by sol-gel and co-precipitation methods for liquid phase oxidation of Cinnamyl alcohol (CnOH) to Cinnamaldehydes (CnHO) using tert-Butyl hydroperoxide (TBHP) as oxidising agent. Spinel oxide catalyst was characterized by different techniques such as X-ray diffraction (XRD), N-2 adsorption-desorption, BET surface area, and X-ray photoelectron spectroscopy (XPS) to understand the structural, physical properties and oxidation state of the catalyst. The result shows that catalyst prepared by sol-gel method was found higher surface area and smaller crystalline size than co-precipitation method. XPS data confirm the formation of Cu2+ in the spinel which helps to improve the catalytic activity of oxidation. This reaction follows radical mechanism, and exhibited 76.7 % of CnOH conversion and 68.4 % of CnHO, and 24.8 % benzaldehyde (benzald) selectivity using TBHP at 60 degrees C. Kinetic data reveal that 41.2 kJ/mol of activation energy for the reaction. The higher activity of spinel oxide catalyst could be due synergetic effect of spinel (88 %) and oxides (12 %) formed in the catalyst, which helps to provide the oxygen during reaction. The contribution of Cu2+ is higher in sol-gel than co-precipitation, which may provide the better reactivity of catalyst. This work helps to select the effective and cost-effective catalyst for the oxidation of CnOH.
Keywords: Catalysts; Cinnamaldehyde; Cinnamyl Alcohol; Cupper; iron; oxide; spinel